STUDENTS’ READINESS ON THE USE OF MEDIA IN LEARNING PROCESS - Elisabeth Marsella; Bekty Sundoro Tandaningtyas (Universitas Negeri Makassar, 2021)
In this era, English plays an important role in opening access to education and career. Regarding the significance, universities in Indonesia not only include English subjects in the curriculum, but they also use the English media for other subjects such as books, presentation slides, and video. This application has been a complaint from students, especially the first-year students who are used to using Indonesian media. Therefore, this study aims to see first-year students’ readiness in using English media for the learning process. This study adopts a mixed-method approach using questionnaires and interviews. The result shows the students feel that they have good English skills, but the learning process using English media has not been optimized. Furthermore, this condition has affected the learning process.